Perkembangan Sosial Emosional Anak Usia Dini Di Raudhatul Athfal Lii Muttaqin - Guswanti, Nelia; Rayahu, Evi; Nurwulan Sari, Dwi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
The research is conducted as the Early Childhood Students at RA Lil Muttaqin Tapung Kampar have problems in socialization, sharing toys, taking turn in playing, expressing the feelings, and lack ability to communicate with peers. This research purpose was to determine the early childhood students’ socio-emotional development levels at RA Lil Muttaqin Tapung Kampar. The research used qualitative research method. The data analysis was used quantitative to test hypotheses. The research was used observation, interviews and documentation techniques. Social Emotional Development is a mental change that takes place gradually and in a certain time, from the simple ability to more complex abilities. Development is a process of changing or improving something towards a complex and psychological nature. Development and growth are two different things but development is related to growth. The indicators of the social emotional development of early childhood students are self-awareness, managing emotions, utilizing emotions productively, empathy, and building relationships. After testing the validity, reliability and descriptive statistics form the early childhood students’ socio-emotional development at RA Lil Muttaqin Tapung Kampar was in “good” category at 9.3 and 130 respectively. The minimum value was 7 and the maximum value was 10 for all indicators. The early childhood students’ socio-emotional development at RA Lil Muttaqin Tapung Kampar was very good